Time-dependent behaviour and modeling of Jinping marble under true triaxial compression. (October 2018) - Zhao, Jun; Feng, Xia-Ting; Zhang, Xiwei; Yang, Chengxiang; Zhou, Yangyi
Abstract: The time-dependent deformation, creep rate, and long-term strength of Jinping marble under different 3-D stress states were studied by using true triaxial creep experiment. A 3-D visco-elastic-plastic creep model, which can describe the accelerated creep， was developed according to the true triaxial time-dependent deformation curve. The results show that the time-dependent behaviour of Jinping marble is affected by the stress level. When the stress is less than the long-term strength, not obvious time-dependent behaviour of the rock sample is found, and the strain remains unchanged after primary creep. When the stress exceeds the long-term strength, the time-dependent behaviour of the rock sample gradually increases with increasing σ 1 and a clear steady state creep stage is seen in the strain-time curve. With constant σ 1 and σ 3, the time-dependent deformation and creep rate in the three main stress directions gradually decrease with increasing σ 2 . Compared with conventional triaxial test data, a large intermediate principal stress increases the time-dependent dilatation in the σ 3 direction. In addition, a 3-D visco-elastic-plastic creep model considering damage is proposed to describe the creep behaviour of hard rock under different 3-D stress states. The model results fit the experimental results, and the selection of model parameters is closely related to the intermediate principal stress. The model results also verify the applicability of the 3-D element model.